Desempenho bioeconômico de diferentes genótipos caprinos em confinamento - Oliveira, Ana Barros de (2014)
This investigation was carried out to evaluate the performance, gross profit margin, morphometric characteristics and not constituent components of housing, of goats of different genetic groups finished in feedlot. The experiment was conducted at the Experimental Station of Dispute, belonging to EMEPA (Agricultural Research Company Paraíba SA), located in the Cariri. Used 30 goats, crossbred (F1) intact male, 10 goats Boer x SPRD (No Defined Breed Standard), 10 x Savannah SRD and 10 Pardo Alpine x SRD, with an average weight of 15 kg and an average age of 100 days at the beginning of the experiment. The design was completely randomized with three treatments (genotypes) and 10 replications. The animals were fed ad libitum diet only, containing approximately 16.5% crude protein and 2.58 Mcalmetabolizable energy per kilogram of dry matter, forage: concentrate ratio of 20:80. The animals were weighed at the beginning of the trial and every 14 days. It was established as slaughter criterion, the average weight of the lot of 25 kg or, if this first criterion was not reached, the maximum period of 64 days of confinement. Evaluated the initial and final body weight, average daily gain, total weight gain, dry matter intake, water intake, feed conversion and days on feed. Were also evaluated the morphometric characteristics and non carcass components. As an economic indicator was calculated, gross profit margin (MB), based on biological and economic parameters. There was no significant effect (P> 0.05) of genetic group on the performance characteristics of goats. There was no significant effect of genetic group (P> 0.05) on the morphometric characteristics analyzed in this study. Was observed Statistical significance (P <0.05) the genetic group only on weight blood and skin . The genetic group had a direct influence on profitability finishing system. Crossbred Boer goats x SPRD provided higher margin gross profit . In the feedlot finishing system crossbred Boer goats x SPRD showed better performance, providing greater profitability to the creator. The evaluated morphometric characteristics suffer no effects of genetic groups. Among the non-carcass components, only skin, blood and head are influenced by genetic group.